2009
DOI: 10.1007/s10734-009-9264-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of new public management instruments on PhD education

Abstract: New public governance emphasises less state, more market and more hierarchy as the cornerstones for effective steering of higher education institutions. Based on an explorative analysis of qualitative and quantitative data of fourteen German and European economics departments, we investigate the steering effects of six new public management instruments in the years 2001 and 2002 on subsequent placement success of PhD graduates. Using crisp set Qualitative Comparative Analysis to analyse the data, our results d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…While Schneider and Sadowski ( 2010 ) reported that an increased competition for resources leads to successful Ph.D. education, our interviewees yet raised the issue that market incentives are not working (as they should) in each context (e.g., in basic research).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Schneider and Sadowski ( 2010 ) reported that an increased competition for resources leads to successful Ph.D. education, our interviewees yet raised the issue that market incentives are not working (as they should) in each context (e.g., in basic research).…”
Section: Discussionmentioning
confidence: 99%
“…First, in an interview study based on scholars from economics departments, Schneider and Sadowski ( 2010 ) investigated how New Public Management affects Ph.D. education. The authors found that different governance mechanisms can be effective, e.g., the increased competition for resources leads to successful Ph.D. education.…”
Section: Current Developments At Higher Education Institutionsmentioning
confidence: 99%
“…The quasi-market competition for research funding and for students serves as a foundation for the success of US university departments (Aghion et al 2009). Schneider and Sadowski (2010) analyzed data pertaining to the employment of doctoral graduates in economics for 2001 and 2002 from 14 universities at Germany and other European countries. According to their analysis, the major characteristics of successful departments are transparency of their academic achievements, no governmental or university regulations, and research funding that is allocated through performance competition.…”
Section: University Reform Experiences Of Advanced Economies and Lmentioning
confidence: 99%
“…Some studies consider the total number of graduates [24], the reputation of a graduate school [5,17] or placement success [35]. The present analysis follows the approach of several studies that consider publication records as performance measure, either for PhD graduates [21] or professors [31].…”
Section: Outcomementioning
confidence: 99%